Library of Congress Subject Headings in Jewish Studies: Recent Changes (1994-1995) - Galron-Goldschliiger, Joseph (Judaica Librarianship, 1995)
The following subject headings of interest to Judaica and Hebraica librarians were culled from Library of Congress Weekly Lists (1994) nos. 6-52 (Feb. 9, 1994–December 28, 1994), and (1995) nos. 1–36 (January 4, 1995-September 6, 1995). This list continues my earlier one, published in Judaica Librarianship, vol. 8, no. 1–2 (Spring 1993–Winter 1994), pp. 73–82. The list is also an update of my 4th edition of Library of Congress Subject Headings in Jewish Studies (New York: Association of Jewish Libraries, 1993).